Prevalencia y factores de riesgo asociados a recesiones gingivales en estudiantes de III a VIII semestre de la universidad Antonio Nariño sede Cúcuta (2023)
Gingival recession is the displacement of the gingival margin beyond the cement-enamel junction, where its prevalence is evident in young adults and studies indicate that its severity increases according to age, presence of precipitating and predisposing factors.